The Prevalence of Post-traumatic Stress Disorder Among Health Care Workers During the COVID-19 Pandemic: An Umbrella Review and Meta-Analysis - Sahebi, Ali; Yousefi, Atefeh; Abdi, Kamel; Jamshidbeigi, Yousef; Moayedi, Siamak; Torres, Mercedes; Wesemann, Ulrich; Sheikhbardsiri, Hojjat; Golitaleb, Mohamad (Frontiers in Psychiatry, 2021)
Introduction: Frontline health care workers (HCWs) have had an increased risk of developing health problems during the COVID-19 pandemic. In addition to physical illness, they have experienced mental health challenges, including post-traumatic stress disorder (PTSD). The aim of this study is to investigate the prevalence of PTSD among HCWs during the COVID-19 pandemic via an umbrella review and meta-analysis. Methods: This study was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline to perform a systematic literature search using various medical databases (Web of science, PubMed, Scopus, Cochrane, ProQuest, Science Direct, Embase, and Google scholar). The search included all articles published through the first of January 2020 the end of March 2021. The systematic review and meta-analysis studies that reported the prevalence of PTSD among health care workers were included in the study, and studies that reported the prevalence of PTSD in normal people or other epidemics were excluded. The random effects model was used to perform a meta-analysis, and the I2 index was used to evaluate heterogeneity among studies. Publication bias was assessed using the Egger test. Data was analyzed using STATA (version 14) software. Results: The initial literature search yielded 145 studies. After excluding duplicates and assessing the quality of the studies, eight studies were selected for meta-analysis. The results showed that the overall prevalence of PTSD among HCWs during the COVID-19 pandemic was 13.52% (95% CI: 9.06-17.98, I2= 65.5%, p= 0.008). Conclusion: There is a high prevalence of PTSD among frontline HCWs during the COVID-19 pandemic. It is important to invest in efforts to screen HCWs for mental health disorders such as PTSD and provide them with mental health support.